Women and the politics of place - Harcourt, Wendy; Escobar, Arturo (2002)
Wendy Harcourt and Arturo Escobar introduce the key concepts discussed in the journal issue. They bring an analysis of women's political organizing in the context of globalization into dialogue with the conceptual work of activist intellectuals engaged in debates about the nature of globalization. - Reproduced.
Keywords: Women